Developing English Speaking Material For Students Of Business And Management Program At Vocational School - Lumbannahor, Berman; Darmahusni, Darmahusni; Suseno, Muchlas (International Journal of Educational Research & Social Sciences, 2023)
The objective of this study was to develop English speaking material based on students’ needs. This study followed the steps of research and development proposed by Borg and Gall. Which are 1) evaluation and need analysis; 2) material development; 3) validation; 4) revision and final production. It was found that 83% students agreed that the existing materials currently used by the students were irrelevant with business and management program.The irrelevance materials were then developed through CTL approach and relevant with their study program and work life situation. The learning materials were developed into 6 units of speaking material. The learning materials were then validated by two experts. The average score of the validation was 88, It showed that learning materials were very good, relevant and feasible.